Educational videos from a film theory perspective: Relating teacher aims to video characteristics. (26th December 2018) - Wijnker, Winnifred; Bakker, Arthur; van Gog, Tamara; Drijvers, Paul
Abstract: Teachers are increasingly using video in their lessons, with various aims (eg, to raise students' levels of conceptual knowledge or interest). Videos that can be used for educational purposes are numerous, ranging from instruction videos to fiction films. Such videos have different characteristics, for example regarding the amount and structure of information, and the audio‐visual presentation. However, guidelines on which video characteristics can help to achieve specific teacher aims are lacking. As a first step towards composing such guidelines, we added a film theory perspective to educational research on videos. The study included seven science teachers, 13 videos, and 233 students (aged 13–18 years). We used teacher interviews, video analyses, student questionnaires and a cross‐case analysis connecting all the data. Data analysis followed a grounded theory approach, including open and axial coding to structure the data, and the constant comparative method to interconnect them. The results showed that videos that posed questions were associated with an increase in students' interest, and that highly informative videos with authoritative speakers were associated with an increase in students self‐reported conceptual knowledge gains. Moreover, teachers often did not have explicit aims for using a particular video, and they selected and used videos in their lessons intuitively. Stimulating teachers to use videos in a more aim oriented way may make video usage more effective. From these findings, we developed a framework to assist teachers in selecting or making videos that match their aims, and a model of possible connections between teacher aims and film types as a first step towards guidelines for teachers using educational videos.